GRAPHIC ORGANIZER VERSUS SENTENCE COMBINING: DETERMINING A STRATEGY FOR TEXT WRITING - Hendi Hidayat (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: This study examines how students with high and low interest who were trained through graphic organizer differ significantly from those who were trained through sentence combining strategy in writing hortatory text. The subjects of the study were the eleventh grader students of MANU Buntet Pesantren Cirebon in the Academic Year of 2015/2016. The population consists of 315. Two of eight classes were selected as the sample of the research. The experiment was set up according to a pre-test and post-test for both experimental and control group. The writer used an experimental research with factorial design 2 x 2 as the research design by technique of multifactor analysis of variance (ANOVA). The findings of this study indicate that graphic organizer is more effective than the sentence combining strategy. It can be seen from the results of both scores in the experimental class that the scores of the post-test have significantly different comparing to the post-test scores in the control group. The writer also found that since learners generally have more background knowledge, graphic organizers bridge what learners already know with what they are learning. Keywords: Graphic organizer, Sentence Combining, Interest, hortatory, experiment.